Public Sector Management Reform in Developing Countries: Perspectives Beyond NPM Orthodoxy. (8th December 2015) - Brinkerhoff, Derick W.; Brinkerhoff, Jennifer M.
Summary: With the passage of time and the accumulation of experience, the hegemony of the New Public Management (NPM) (now no longer new) as the dominant approach to public sector reform has weakened, particularly as applied to developing countries. What alternative frameworks for theory and practice offer insights and guidance beyond the NPM orthodoxy? This article offers some answers to this question and draws upon the contributions to this special issue to explore four analytic strands that constitute post‐NPM approaches to reform: political economy and institutions, public management function over form, iterative and adaptive reform processes, and individual and collective agency. The discussion highlights the significance of functional mimicry, the challenges of measuring results, the practical difficulties in achieving contextual fit and accounting for the inherent uncertainty in reform processes, the tensions between ownership and outside expertise, and unpacking political economy dynamics within various micro‐contexts and across regime types. Copyright © 2015 John Wiley & Sons, Ltd.